PEMODELAN SPASIAL DALAM MENGIDENTIFIKASI TINGKAT KERENTANAN BANJIR DI KECAMATAN MEJOBO, KABUPATEN KUDUS, JAWA TENGAH, INDONESIA - Eka Wulan Safriani; Somantri, Lili; Rohmat, Dede; Setiawan, Iwan; Panjaitan, Budi Rahmah; Arifin, A (Jurnal Tanah dan Sumberdaya Lahan, 2024)
The occurrence of flood disasters is an annual unavoidable event in the Mejobo District, Kudus Regency. This study aims to map the vulnerable areas to floods in the Mejobo District using spatial modelling. The parameters used to determine the vulnerability areas include soil type, elevation, population density, river buffer, rainfall, and land use. The research location is situated in the Mejobo District. The research method employed is the models and multicriteria decision-making (MCDM) techniques, with the assistance of ArcGIS software for data processing and analysis. The research findings yield a final map depicting flood vulnerability, which indicates the distribution of flood-prone areas. Areas with a high level of flood vulnerability are dispersed across agricultural fields and areas adjacent to rivers, covering an area of 1,770 hectares. Meanwhile, areas with a moderate level of vulnerability are predominantly distributed in residential areas, covering an area of 1,907 hectares.